2016
DOI: 10.1128/msphere.00215-16
|View full text |Cite
|
Sign up to set email alerts
|

The Denture-Associated Oral Microbiome in Health and Stomatitis

Abstract: Denture stomatitis is a prevalent inflammatory condition of the mucosal tissue in denture wearers that is triggered by microorganisms. While Candida has been extensively studied for its role in stomatitis etiology, the bacterial component largely remains to be investigated. Our data show that certain types of bacteria are significantly associated with denture health and disease. Furthermore, the bacterial communities residing on the teeth and dentures of the same person are similar to each other independently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 61 publications
2
51
0
1
Order By: Relevance
“…Our data indicates that the alpha diversity of the salivary microbiome in the control groups was significantly higher in comparison to those suffering from poor oral health, which is similar to previously reported results [64]. Our data show that usage of denture is positively correlated with age and is closely linked with the oral health status [65]. In this study, we show that using denture reduces the diversity of the salivary microbiome with an enrichment of both Proteobacteria and Actinobacteria phyla while Streptococcus and Neisseria were enriched at the genus levels.…”
Section: Discussionsupporting
confidence: 91%
“…Our data indicates that the alpha diversity of the salivary microbiome in the control groups was significantly higher in comparison to those suffering from poor oral health, which is similar to previously reported results [64]. Our data show that usage of denture is positively correlated with age and is closely linked with the oral health status [65]. In this study, we show that using denture reduces the diversity of the salivary microbiome with an enrichment of both Proteobacteria and Actinobacteria phyla while Streptococcus and Neisseria were enriched at the genus levels.…”
Section: Discussionsupporting
confidence: 91%
“…Alterations of the oral cavity condition in reaction to an intraoral prosthesis may cause lack of saliva accessibility and tongue-associated mechanical cleansing [24]. Furthermore, dentures can harbor mixed kinds of [25,26]. 18 kinds of bacteria were isolated from denture plaque that can induce respiratory infection in elderly [19,27].…”
Section: Discussionmentioning
confidence: 99%
“…Ahn et al in a study examining saliva in dentate subjects showed the 10 most common genera in the oral microbiome were Streptococcus, Veillonella, Leptotrichia, Prevotella, Haemophilus, Capnocytophaga, Rothia, Gamella, Neisseria, and Lactococcus , a result supported by other similar studies (Ahn, Chen, & Hayes, ; Bik et al, ; Keijser et al, ). Others have examined the oral microbiome of edentulous patients, though this was done consistently with dentures in place (Marsh, Percival, & Challacombe, ; O'Donnell et al, ; Sachdeo, Haffajee, & Socransky, ; Shi et al, ). An early study showed that denture wearers produced saliva with more abundance of Lactobacilli, Staphylococci, Streptococci , and yeast than dentate subjects (Marsh et al, ).…”
Section: Introductionmentioning
confidence: 99%